Technology licensing by advertising supported media platforms: An application to internet search engines - Geza Sapi; Irina Suleymanova (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2011)
We develop a duopoly model with advertising supported platforms and analyze incentives of a superior firm to license its advanced technologies to an inferior rival. We highlight the role of two technologies characteristic for media platforms: The technology to produce content and to place advertisements. Licensing incentives are driven solely by indirect network effects arising fromthe aversion of users to advertising. We establish a relationship between licensing incentives and the nature of technology, the decision variable on the advertiser side, and the structure of platforms' revenues. Only the technology to place advertisements is licensed. If users are charged for access, licensing incentives vanish. Licensing increases the advertising intensity, benefits advertisers and harms users. Our model provides a rationale for technology-based cooperations between competing platforms, such as the planned Yahoo-Google advertising agreement in 2008.
Keywords: L13; L24; L86; M37; 330; Technology Licensing; Two-Sided Market; Advertising; Suchmaschine; Online-Werbung; Informationstechnik; Lizenzvergabe; Coopetition; Theorie